Antioxidant Activity Evaluation of Polar, Semi-Polar, and Non-Polar Fractions of Custard Apple (Annona Squamosa L.) Leaf Extract Using the DPPH Method - Suhelmiah; Pomeistia, Meilynda; Rahayu, Lale Budi Hutami; Rahayu, Supiani (Balai Publikasi Indonesia, 2026)
Antioxidants are compounds that can donate hydrogen atoms to free radicals so that they can stop the chain reaction and convert free radicals into a stable form. custard apple leaves are known to have various benefits, one of which is as an antioxidant. This study aims to determine the potential antioxidant activity contained in custard apple leaves (Annona Squamosa L) with polar, semi-polar and non-polar fractions through the DPPH method. The sample used in this study was custard apple leaf extract (Annona Squamosa L) extracted with 96% ethanol solvent, and phytochemical screening tests, fractionation, antioxidant activity tests using UV-Vis spectrophotometer and IC50 value calculation using Microsoft exel were carried out. The results of the sample phytochemical screening showed that there were four compounds, namely phenolics, flavonoids, tannins and alkaloids while the results of the antioxidant activity test had a very strong category with the IC50 value of ethyl acetate, n-hexane and aquadest fractions of (3.950, 4.651, and 11.009 ppm) and the activity results of the IC50 value of custard apple leaf ethanol extract with a strong category of 22.280 ppm.